Analysis of Emotional Intelligence on Nurse Performance - Rahayu Winarti (Sean Institute, 2023)
Emotional Intelligence is a concept that has a multidimensional concept that combines cognition with emotion in the means of communication. The emotional Intelligence of nurses has a direct effect on the quality of services provided. Therefore nurses who have high emotional Intelligence can provide quality services. This study aimed to determine the relationship between emotional Intelligence and nurse performance in applying nursing care. This type of research uses quantitative methods with a cross-sectional analytical approach. This research instrument uses two instruments, emotional Intelligence, and nurse performance, that have been tested for validity and reliability by other researchers. The sample of this study was 47 respondents. The result of p-value = 0.000 and rho value = 0.963, Ha is accepted. This suggests there is a relationship between emotional Intelligence and nurse performance. Ha is accepted, which means there is a relationship between emotional Intelligence and the Performance of adolescent nurses in Baitul Izzah Room 1 and 2 RSI Sultan Agung Semarang.